Language And Culture: Ujung Tradition As One Of The Methods Of Understanding Culture - Sigit Haryanto (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Understanding culture may through many methods. One of them is custom and tradition.Tradition that is selected to know the culture is ujung tradition. It is Javanese heritagethat is still acted in Surakarta and its vicinity. This tradition deals with Eid Al-Fitr. Themain activities are visiting to parents, neigbors, and society with happily holiday. One ofthe main focuses is what the ideas are in it. The data that were colleted by participantobservation and depth interview then analysed by using descriptive analytics have resultsas follows: the ideas in ujung traditions are manners, respect, alms, friendship, andconfession of sin. Seeing that many positive ideas in ujung tradition, it is suggested to bepreserved and thaught to the children.